The H2O Southern Galactic Plane Survey (HOPS) – I. Techniques and H2O maser data - Walsh, Andrew; Breen, S.; Britton, T.; Brooks, K.; Burton, M.; Cunningham, M.; Green, J.; Harvey-Smith, L.; Hindson, L.; Hoare, M.; Indermuehle, B.; Jones, P.; et al. (Oxford University Press, 2011)
We present first results of the H2O Southern Galactic Plane Survey (HOPS), using the MopraRadio Telescope with a broad-band backend and a beam size of about 2 arcmin. We haveobserved 100 deg2 of the southern Galactic plane at 12mm(19.5–27.5 GHz), including spectralline emission from H2O masers, multiple metastable transitions of ammonia, cyanoacetylene,methanol and radio recombination lines. In this paper, we report on the characteristics of thesurvey and H2O maser emission. We find 540 H2O masers, of which 334 are new detections.The strongest maser is 3933 Jy and the weakest is 0.7 Jy, with 62 masers over 100 Jy. In 14maser sites, the spread in the velocity of the H2O maser emission exceeds 100 km s-1. Inone region, the H2O maser velocities are separated by 351.3 kms-1. The rms noise levelsare typically between 1 and 2 Jy, with 95 per cent of the survey under 2 Jy. We estimatecompleteness limits of 98 per cent at around 8.4 Jy and 50 per cent at around 5.5 Jy. Weestimate that there are between 800 and 1500 H2O masers in the Galaxy that are detectable ina survey with similar completeness limits to HOPS. We report possible masers in NH3 (11,9)and (8,6) emission towards G19.61-0.23 and in the NH3 (3,3) line towards G23.33-0.30.